2019
DOI: 10.1002/ijc.32531
|View full text |Cite
|
Sign up to set email alerts
|

A tumor‐targeting nanomedicine carrying the p53 gene crosses the blood–brain barrier and enhances anti‐PD‐1 immunotherapy in mouse models of glioblastoma

Abstract: Despite its anticipated clinical potential, anti‐PD‐1 immunotherapy has only yielded poor outcomes in recent clinical trials for glioblastoma patients. Strategies combining anti‐PD‐1 antibody with other treatment modalities are being explored to alter the immunosuppressive microenvironment that appears to characterize these anti‐PD‐1‐insensitive tumors. Here, we evaluated whether introducing wild‐type p53 gene via a tumor‐targeting nanomedicine (termed SGT‐53) could provide immune stimulation and augment anti‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…Usually, tumor cells are injected subcutaneously, as it is easier to track tumor development [25]. In order to make TME closer to that of people, the tumor cells can be orthotopically transplanted into the corresponding organs [26], such as intravenous administration of leukemia and lymphoma cells [27], injection of breast tumor cell lines into mammary adipose tissue [28], intrapancreatic injection of pancreatic duct adenocarcinoma [29], and intracranial injection for glioblastoma cell lines [30,31]. These administration routes more accurately reflect TME, but require more complicated manipulations and special equipment for both the transplantation and monitoring of the further tumor development [32].…”
Section: Syngeneic Tumor Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually, tumor cells are injected subcutaneously, as it is easier to track tumor development [25]. In order to make TME closer to that of people, the tumor cells can be orthotopically transplanted into the corresponding organs [26], such as intravenous administration of leukemia and lymphoma cells [27], injection of breast tumor cell lines into mammary adipose tissue [28], intrapancreatic injection of pancreatic duct adenocarcinoma [29], and intracranial injection for glioblastoma cell lines [30,31]. These administration routes more accurately reflect TME, but require more complicated manipulations and special equipment for both the transplantation and monitoring of the further tumor development [32].…”
Section: Syngeneic Tumor Modelsmentioning
confidence: 99%
“…Syngeneic tumor models are also used to investigate the antitumor activity of ICIs, including anti-cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) [39] and anti-programmed death (PD)-1 anti-PD-L1 antibodies [31,40]. For example, using the syngeneic model of immunocompetent B6 mice transplanted with E.G7 hematopoietic cell line or its analogue with PD-L1 deficiency it has been shown that the PD-L1 pathway blockade contributed to the rejection of tumor cells in mice transplanted with both wild-type (WT) E.G7 cells or PD-L1 deficient E.G7 cells in the same degree.…”
Section: Syngeneic Tumor Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with newly diagnosed resectable glioblastoma, administration of adenovirus-mediated gene therapy containing the prodrug converting enzyme sitimagene ceradenovec followed by intravenous administration of the antiviral drug ganciclovir increases the mortality rate in patients, but does not increase overall survival [ 148 ]. Interestingly, gene therapy is being proposed as a valuable adjuvant for current glioblastoma treatment [ 149 151 ]. Supporting this approach, Speranza et al utilized a nonreplicating adenovirus containing the HSV TK gene (AdV-tk) to enhance anti-PD-1 efficacy in syngeneic glioblastoma-bearing mouse models [ 152 ].…”
Section: Nanomedicine-based Combination Therapies For Glioblastomamentioning
confidence: 99%
“…Multiple kinds of gene therapies have been developed to cure brain cancers, including suicide gene therapy, cytokine-mediated gene therapy, tumor suppressor gene therapy and oncolytic gene therapy [7][8][9][10]. Among them, suicide gene therapy is the most frequently used approach to cure glioma both in preclinical studies and in clinical trials [11].…”
Section: Introductionmentioning
confidence: 99%